2005
DOI: 10.1093/hmg/ddi097
|View full text |Cite
|
Sign up to set email alerts
|

MeCP2 deficiency in Rett syndrome causes epigenetic aberrations at the PWS/AS imprinting center that affects UBE3A expression

Abstract: Rett syndrome (RS) is a severe and progressive neurodevelopmental disorder caused by heterozygous mutations in the X-linked methyl CpG binding protein 2 (MeCP2) gene. MeCP2 is a nuclear protein that binds specifically to methylated DNA and functions as a general transcription repressor in the context of chromatin remodeling complexes. RS shares clinical features with those of Angelman syndrome (AS), an imprinting neurodevelopmental disorder. In AS patients, the maternally expressed copy of UBE3A that codes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 37 publications
0
94
1
2
Order By: Relevance
“…As expected from the mouse studies, a significant defect in GABRB3 transcript was observed in RTT brain compared to control ( Figure 3A). Although conflicting data have been reported on the dysregulation of Ube3a in Mecp2-deficient mouse (13,31,32), a significant decrease in UBE3A expression was found in RTT brain ( Figure 3B), consistent with the decreased protein observed previously (13). Even though MeCP2 binds to the promoter of SNRPN (13,26), no difference in SNRPN transcript was observed ( Figure 3C), consistent with maintenance of normal imprinting of SNRPN in RTT (33), and normal expression in Mecp2-deficient mouse brain (13,34).…”
Section: Resultsmentioning
confidence: 99%
“…As expected from the mouse studies, a significant defect in GABRB3 transcript was observed in RTT brain compared to control ( Figure 3A). Although conflicting data have been reported on the dysregulation of Ube3a in Mecp2-deficient mouse (13,31,32), a significant decrease in UBE3A expression was found in RTT brain ( Figure 3B), consistent with the decreased protein observed previously (13). Even though MeCP2 binds to the promoter of SNRPN (13,26), no difference in SNRPN transcript was observed ( Figure 3C), consistent with maintenance of normal imprinting of SNRPN in RTT (33), and normal expression in Mecp2-deficient mouse brain (13,34).…”
Section: Resultsmentioning
confidence: 99%
“…64 Given the possible contribution of epigenetic factors to autism, researchers have examined interactions involving genes from imprinted regions of chromosome 15q. There has been some evidence that Mecp2 regulates Ube3A and Gabrb3 expression in the mouse model for Rett syndrome, 87,344 but this finding has been inconsistent. 345 There are also reports that Mecp2 plays a role in the regulation of Bdnf levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, association of methyl-CpG-binding domain (MBD) proteins to the methylated allele could be involved in somatic maintenance, as well as the recruitment of enzymatic complexes that regulate histone modifications linked to the differential DNA methylation. (9,39,40) When do the aberrant epigenetic alterations occur in SRS and BWS? Several observations suggest that these arise after fertilisation, at some point early in development.…”
Section: Introductionmentioning
confidence: 99%